Current trends in the treatment of primary mediastinal large B-cell lymphoma – an overview - Petković, Ivan (Contemporary Oncology/Współczesna Onkologia, 2015)
Primary mediastinal large B-cell lymphoma has been recognised as a distinct entity with unique clinical, pathologic, and genetic features. According to WHO 2008 classification it is marked as a variant of diffuse large B-cell lymphoma but shares characteristics with classic Hodgkin lymphoma. Genetic analysis has shown that amplification of the 9p24.1 region is the disease’s specific structural alteration. Aggressive behaviour and a tendency to invade surrounding tissues of the thoracic cavity, often causing superior vena cava syndrome, or pleural or pericardial effusions, are the clinical hallmarks of this disease. For a long period of time it has been considered as a disease with poor prognosis, which responds poorly to the conventional treatment created for diffuse large B-cell lymphoma. An elective treatment has not yet been established, but recently the situation has became much more favourable. After the introduction of rituximab the cure rates have risen to over 80%, and the most recent results have demonstrated a new insight with dose-adjusted intensified continuous treatments, in which the cure rates have exceeded 90%. Current trends have led to the introduction of dose-adjusted intensified protocols becoming a standard of care, whereas the use of radiotherapy remains controversial because of the questionable predictive value of post-treatment PET/CT validity. The relapse rate is very low after two years of sustained complete remission. If the disease relapses or is resistant the outcome is very poor regardless of the applied treatment modality.